10−7 M genistein partially alleviates 10−7 M MEHP unfavorable effects in a new modified fetal rat testis culture system - Zhang, Tong-Dian; Ma, Yu-Bo; Gao, Ming; Li, He-Cheng; Wang, Zi-Ming; Chong, Tie; Zhang, Lian-Dong (Frontiers in Cell and Developmental Biology, 2022)
Background: Recent studies revealed that some common endocrine-disrupting chemicals (EDCs) including phthalates and phytoestrogens may exhibit low-dose effects properties. However, how low dose of these EDCs and their mixture would affect fetal rat testis development still needs further investigation. Moreover, testis organ culture system also needs further modification to provide an effective tool for ex vivo EDCs study. Methods: We firstly modified the agarose organ culture system, in which fetal rat testes were cultured for 4 days (d1 to d4) on agarose gels held by Millicell inserts. Then we used the modified agarose culture system to study the combined effects of multiple EDCs exposure. 15.5dpc fetal rat testes were isolated and treated with vehicle, MEHP (0.1μmol/l), GEN (0.1μmol/l) or MEHP (0.1 μmol/l) + GEN (0.1μmol/l). Parameters concerning testicular cell development and function were evaluated, trying to gain insight into the early molecular events after multiple EDCs exposure. Results: The development of somatic，germ cells and seminiferous tubule in 15.5dpc fetal rat testis was better sustained in the modified agarose culture system . Based on the modified system, we found that MEHP at 0.1μmol/l induced alterations in gonocyte markers, antioxidative enzyme activity as well as transient reduction of testosterone production, accompanied by mitochondria swelling in gonocytes and Sertoli cells. No obvious morphological and histological alterations were observed in all treated groups. However, coadministration of genistein at 0.1μmol/l partially alleviated MEHP-induced fetal testis damage ex vivo through enhancement of antioxidative action. MEHP at low dose still showed weak endocrine disrupting properties but did not exhibit typical low-dose effects. Conclusion: Our findings indicated that the modified agarose culture system could better mimic testicular microenvironment without obvious hypoxic cell damage. Furthermore, low dose of MEHP induced mild disruption to fetal testis development, cotreatment of genistein at low dose attenuated MEHP induced fetal testis injuries in part by balancing redox state, indicating that low dose of genistein may partially protect fetal testis from phthalates induced injury.